A guide for respiratory physiotherapy postgraduate education: presentation of the harmonised curriculum. Issue 6 (6th June 2019) - Troosters, Thierry; Langer, Daniel; Burtin, Chris; Chatwin, Michelle; Clini, Enrico M.; Emtner, Margareta; Gosselink, Rik; Grant, Kathleen; Inal-Ince, Deniz; Lewko, Agnieszka; Main, Eleanor; Oberwaldner, Beatrice; et al.
Harmonising education is one of the most important challenges to ensure mobility of healthcare professionals across countries and regions of the world. While patients are affected by the same diseases, the healthcare systems in which they are cared for are very different and the healthcare providers within these systems are trained very differently. Health education in many countries is largely based on tradition. This is true for most medical specialities, as well as for physical therapy education [1], including respiratory physiotherapy. The responsibilities and the degree of professional and academic training vary widely across countries and regions [2]. While all educational programmes are probably fit for purpose within a given healthcare system, the variability in knowledge, skills and attitudes makes mobility and cross-certification difficult, if not impossible. In addition, the growing body of evidence for respiratory physiotherapy [3] makes it all the more important to foresee a framework for postgraduate training that prepares the workforce for the future [4]. For a global organisation, such as the European Respiratory Society (ERS), it also challenging to design postgraduate education that matches the level of knowledge and skills of all members. The ERS has a long tradition of providing such frameworks for harmonised education and training in respiratory medicine [5]. Figure 1 provides an overview of all available curricula and certified training programmes. The ERS respiratory physiotherapy curriculum sets a new standard for postgraduate respiratory physiotherapy education. It was developed to promote evidence-based practice and physical skills for the respiratory physiotherapist. http://bit.ly/2LwJ0mb